ENDOMETRITIS IN MARES DUE TO COLIFORM AND ITS SUCCESSFUL TREATMENT - ASSAD, NAFIS I; PANDEY, ANAND KUMAR (The Indian Journal of Animal Reproduction, 2023)
Five broodmares with history of persistent endometritis and repeat breeding for last two breeding seasonswere examined for their reproductive health by ultrasonography and the uterine samples were aseptically collectedusing low-volume flush technique by two-way Foley's catheter. The uterine samples were found positive forEscherichia coll upon culture. The mares were treated with a treatment regimen consisting of uterine lavage withnormal saline+ Cloprostenol (250μg, i.m.) + intrauterine antibiotic infusion based on the antibiotic sensitivity test.All mares revealed absence of uterine exudates and/or uterine wall thickening upon post-treatment ultrasound.The mares conceived after the treatment, four in the 1st artificial insemination (Al) and other in 2nd Al.
Keywords: Coliform endometritis; Intrauterine infusion; Mares; Treatment; Uterine infection